Գեռլայի հայերի մշակույթը և արվեստը - Թարվերդյան, Հեթում քահանա («Նաիրի» հրատ.)
Армяне начали селиться в Трансилвании в X-XIV веках. Примечательно, что армянская община Молдавии подверглясь гонениям и была вынуждена искать убежища в соседних местностях, в основном в Трансилвании. Армяне Трансилвании оставили прекрасные произведения искусства, а город Герла достоин особого внимания с точки зрения истории искусства. Однако из-за разрушений нового времени лишь один образец настенной живописи, имевшей широкое распространение в Арменополисе (Герлы) в XVIII веке, сохранился до наших дней. И только часть этой знаменитой настенной живописи, сделанной в 1723 году, удачно реставрирована и в насоящее время хранится в церкви Соломона. Армянская община Герлы сохранила также солидное число картин на холсте; больщинство из них находится в церкви Святой Троицы, а также в здании районной администрации Армянской Католической церкви. 13 живописных картин зарегистрировано в описи Музея истории Герлы и хранятся там. Исключением является знаменитое полотно «Снятие с креста», которое музей передал церкви Святой Троицы. Коллекция живописи, принадлежащая к армянской общине Герлы включает в себя рая произведений искусства, за немногими исключениями датируемых XVIII и XIX веками. Armenians started to settle in Transylvania between the X and XIV centuries. Noteworthy is the fact that the Armenian community of Moldova, facing persecutions, has been forced to seek shelter in the neighbouring areas and has fled mainly to Transylvania. The Armenians of Transylvania have left wonderful pieces of art. Especially the city of Gherla has a lot to offer to the history of Art. But because of the destructions in modern times, only one of the examples of the mural paintings tradition widespread in the town of Armenopolis (Gherla) in the XVIII century, has survived to our days. And only one part of that famous mural painting made in 1723 is successfully restaurated and is currently kept in the church of Solomon. The Armenian community of Gherla has kept a significant number of canvas paintings, the majority of which is in the church of Saint Trinity, and in the house of the Armenian Catholic church‟s district administration. 13 paintings are registered in the inventory of the History Museum of Gherla and are kept there. An exception is the famous canvas of the “Descent from the Cross.” The Museum has handed it to the church of Holy Trinity. The collection of canvas paintings belonging to the community of Gherla includes а series of works of art, with just a few exceptions dating back to the XVIII and XIX centuries.
Keywords: Արվեստ; Մշակույթ